2011
DOI: 10.1111/j.1600-0412.2011.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of medico‐legal findings on charge filing in cases of rape in adult women

Abstract: Objective. To assess the impact of the medical documentation and biological trace evidence in rape cases on the legal process. Design. Retrospective descriptive study. Setting and sample. Police-reported cases of rape of women ≥16 years old in the Norwegian county of Sør-Trøndelag from January 1997 to June 2003. Methods. Police data were merged with data from the Sexual Assault Center at St Olav's Hospital. Charged and non-charged cases were compared. Main Outcome Measures. Medico-legal findings and legal outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
3
19
1
Order By: Relevance
“…In our study, extragenital injuries alone are observed in almost half of the victims in accordance with four studies [1,18,21,22]. Other studies [3,5,19,[23][24][25] range from 11% and up to 78%. About one-fifth of the victims had both extra-genital and anogenital injuries and this corresponds to the result in three other studies [18,24,25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, extragenital injuries alone are observed in almost half of the victims in accordance with four studies [1,18,21,22]. Other studies [3,5,19,[23][24][25] range from 11% and up to 78%. About one-fifth of the victims had both extra-genital and anogenital injuries and this corresponds to the result in three other studies [18,24,25].…”
Section: Discussionsupporting
confidence: 91%
“…Altogether, 77% of the victims in our study population had been drinking alcohol prior to the assault, which is higher than most studies [3,5]. There is an association between being assaulted by a stranger or by a person the victim has just met if the victim drinks more than 5 units.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The presence of anogenital injuries has been shown to be a major contributing factor in the various decision-making points from a criminal justice perspective [33]. Even though a recent study from Norway found that the documentation of injuries was not associated with charge filing [34], several studies have reported that conviction rates are higher when there is evidence of genital injuries [35,36,37]. The doctor is often asked to make a statement as to whether the intercourse was consensual or non-consensual, thereby providing support for the common misconception, both among the general public and among legal experts, that sexual assault is invariably associated with physical injuries.…”
Section: Injuriesmentioning
confidence: 99%
“…The presence of semen is also a factor that positively influences the filing of a complaint ( p = 0.035)—although it is not really statistically significant—because semen contains the DNA of the aggressor, who thus cannot deny that the event took place , hence the need for a medical examination to be performed as soon as possible, since the probability of finding semen decreases daily, reaching zero after 12 days .…”
Section: Discussionmentioning
confidence: 99%